Evaluation of methodologies for chemical characterization of vinasse as a function of storage time - Batista-Ventura, Hellen Regina Fernandes; Ventura, Matheus Vinicius Abadia; Menezes Filho, Antonio Carlos Pereira de; Oliveira Júnior, Antônio Carlos de; Alves, José Milton (Brazilian Journal of Science, 2022)
The objective of this study was to evaluate efficient analytical methods of wet digestion using the official method of analysis, a mixture of nitric acid and perchloric acid (HNO3 + HClO4), for the analysis of vinasse and also verify the effects of nutrients on stored vinasse. The analytical methods compared were: 1) Nitroperchloric (HNO3), 2) Nitric (HNO3); 3) Chloridric + Hydrogen Peroxide (HCl + H2O2); 4) Sulfuric + Hydrogen Peroxide (H2SO4 + H2O2) and 5) Solubilization with 1 molar Chloridric acid (HCl 1 Mol L-1). Phosphorus, potassium, calcium, magnesium and sulfur were determined over different storage periods, and these nutrients were analyzed at 5, 30, 90 and 150 days of storage, to verify the behavior of these nutrients over the time they are stored in laboratory conditions. The efficiency of the methods was evaluated by comparing the results of the nitroperchloric method obtained for each nutrient with the results obtained from the other methods. The results showed that the nitric (HNO3) and chloridric + hydrogen peroxide (HCl + H2O2) digestions presented good to excellent precision equivalent to the nitroperchloric digestion (HNO3) for the analyzed nutrients. The solubilization method with 1 molar chloridric acid (HCl 1 Mol L-1) presented a low accuracy and did not present the expected efficiency for quantification of any analyzed nutrient. With the exception of potassium contents, all the other nutrients analyzed in the study reduced at the end of the vinasse storage days.